Structure and Electrochemical Properties of a Mechanochemically Processed Silicon and Oxide-Based Nanoscale Composite as an Active Material for Lithium-Ion Batteries - Norihiro Shimoi; Kazuyuki Tohji (Journal of Nanotechnology)
Si is essential as an active material in Li-ion batteries because it provides both high charge and optimal cycling characteristics. A composite of Si particles, Cu particles, and pure H2O was realized to serve as an anode active material and optimize the charge–discharge characteristics of Li-ion batteries. The composite was produced by grinding using a planetary ball mill machine, which allowed for homogenous dispersion of nanoscale Cu3Si as Si–Cu alloy grains and nanoscale Si grains in each poly-Si particle produced. Furthermore, some Si particles were oxidized by H2O, and oxidized Si was distributed throughout the composite, mainly as silicon monoxide. As a result, each Si particle included silicon monoxide and conductive Cu3Si materials, allowing for effective optimization of the recharging and charge-discharge characteristics. Thus, a new and simple process was realized for synthesizing a Si active material composited with silicon oxides, including silicon monoxide. This Si-rich conductive material is suitable as an anode for Li-ion batteries with high charge and optimized cycling properties.